Identification of specific microRNA–messenger RNA regulation pairs in four subtypes of breast cancer. Issue 3 (1st June 2020) - Guo, Ling; Zhang, Aihua; Xiong, Jie
Abstract : Four subtypes of breast cancer, luminal A, luminal B, basal‐like, human epidermal growth factor receptor‐enriched, have been identified based on gene expression profiles of human tumours. The goal of this study is to find whether the same groups' genes would exhibit different networks among the four subtypes. Differential expressed genes between each of the four subtypes and the normal samples were identified. The overlaps between the four groups of differentially expressed genes were used to construct regulations networks for each of the four subtypes. Univariate and multivariate Cox regressions were employed to test the genes in the four regulation networks. This study demonstrated that the common genes in four subtypes showed different regulation. Also, the hsa‐miR‐182 and decorin pair performs different functions among the four subtypes of breast cancer. The result indicated that heterogeneity of breast cancer is not only reflected in the different expression patterns among different genes, but also in the different regulatory networks of the same group of genes.